2019
DOI: 10.1111/1462-2920.14816
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐resolved viral and cellular metagenomes revealed potential key virus‐host interactions in a deep freshwater lake

Abstract: Summary Metagenomics has dramatically expanded the known virosphere, but freshwater viral diversity and their ecological interaction with hosts remain poorly understood. Here, we conducted a metagenomic exploration of planktonic dsDNA prokaryotic viruses by sequencing both virion (<0.22 μm) and cellular (0.22–5.0 μm) fractions collected spatiotemporally from a deep freshwater lake (Lake Biwa, Japan). This simultaneously reconstructed 183 complete (i.e., circular) viral genomes and 57 bacterioplankton metagenom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 110 publications
(172 reference statements)
1
41
0
Order By: Relevance
“…Based on VIRBANT annotations (Supplementary Table 12 ), the most common AMG related to sulfur metabolism within the viral contigs was phosphoadenosine phosphosulfate reductase (PAPS reductase or CysH), which is predicted to participate in assimilatory sulfate reduction. Viral cysH has also been found in viral sequences obtained from oxygen-deficient water columns [ 83 ], rumen [ 84 ], a deep freshwater lake [ 16 ] and sulfidic mine tailings [ 85 ]. Here, we manually confirmed that three vOTUs from two distinct viral genera encoded PAPS reductase genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on VIRBANT annotations (Supplementary Table 12 ), the most common AMG related to sulfur metabolism within the viral contigs was phosphoadenosine phosphosulfate reductase (PAPS reductase or CysH), which is predicted to participate in assimilatory sulfate reduction. Viral cysH has also been found in viral sequences obtained from oxygen-deficient water columns [ 83 ], rumen [ 84 ], a deep freshwater lake [ 16 ] and sulfidic mine tailings [ 85 ]. Here, we manually confirmed that three vOTUs from two distinct viral genera encoded PAPS reductase genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These methods have greatly advanced viral ecology from the identification of novel viruses to the global distribution of viruses. Studies from a variety of environments such as thawing permafrost [ 13 ], mangroves [ 14 ], arctic lakes [ 15 ], freshwater lakes [ 16 ], deep sea sediments [ 17 ], the terrestrial subsurface [ 18 , 19 ], and especially seawater [ 20 22 ] have suggested that prokaryotic viruses act as key agents in natural ecosystems via a range of interactions with their microbial hosts. Viruses can influence organic carbon and nutrient turnover by top-down control of microbial abundance via lysis of cells and subsequent release of cellular contents during lytic infection [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies that have compared levels of lake viral diversity over depth. A study from Lake Biwa (38) reported that Ͼ65% of viral genomes were unique to a particular depth. Similarly to Lake A data, a study of Lake Shunet, a sub-Arctic meromictic lake in Siberia (39), showed that very few viral taxa were present throughout the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating freshwater viromes have resulted in the observation of sharp differences in viral diversity driven by season (27,42,43) or by proximity to the shore or large water inputs or human perturbation (40,44). Several studies have identified salinity as the primary driver of viral diversity (38,45), where higher diversity corresponded with higher conductivity (45,46). Watkins et al (40) proposed that freshwater viral communities are likely to be more diverse than marine viral communities because freshwater environments are generally more heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the distribution and abundance patterns of the recovered PMP MAVGs, the genomes were recruited using BLASTN (96) against the Tara Oceans metagenomes (40,91), Geotraces cellular metagenomes (41), and the Mediterranean metagenomes described previously (14,39). PMP group PMP-D were also recruited against the virome data sets they were recovered from (97) and against samples from other freshwater environments (Lake Biwa [98], Lake Simoncouche [99], Lake Kivu [GOLD Study identifier {ID} Gs0127566], Baltic Sea [100]). Normalization was performed by calculating RPKG (reads recruited per kilobase of the genome per gigabase of the metagenome) so recruitment values could be compared across samples.…”
Section: Methodsmentioning
confidence: 99%